2006
DOI: 10.1097/01.tp.0000226070.74443.fb
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adult Transplant Recipients More than 15 Years after Kidney Transplantation

Abstract: More than 15 years after renal transplantation, recipients present satisfactory HQOL comparable to the general healthy population or at least to pretransplant patients. Vocational rehabilitation following renal transplantation is of highest importance among long-term survivors and is associated with improved HQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
120
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 13 publications
3
120
1
4
Order By: Relevance
“…This is supported by cross-sectional studies which found that patients are less fatigued after kidney transplantation compared to patients before transplantation [5,6]. Even though fatigue seems to decrease after kidney transplantation, sparse studies indicate that kidney transplant recipients (KTRs) experience more fatigue than healthy controls [7,8]. Rodrigue et al [6] even classified 59% of recipients with high fatigue severity, based on an earlier defined cutoff score for clinically relevant fatigue determined in a sample of healthy women [9].…”
Section: Introductionmentioning
confidence: 61%
“…This is supported by cross-sectional studies which found that patients are less fatigued after kidney transplantation compared to patients before transplantation [5,6]. Even though fatigue seems to decrease after kidney transplantation, sparse studies indicate that kidney transplant recipients (KTRs) experience more fatigue than healthy controls [7,8]. Rodrigue et al [6] even classified 59% of recipients with high fatigue severity, based on an earlier defined cutoff score for clinically relevant fatigue determined in a sample of healthy women [9].…”
Section: Introductionmentioning
confidence: 61%
“…19 Thus, exploration of better ways of informing patients about KT, particularly older adults, is needed, especially as indications for transplantation expand [20][21][22] and survival and quality of life improve after transplantation. [23][24][25][26][27] Finally, interventions to improve information disclosure and patient-provider communication may be useful in discussion of transplantation with patients initiating hemodialysis, because these have shown benefit in patient comprehension of treatment options, risks, and benefits in other clinical settings. 8 …”
Section: Discussionmentioning
confidence: 99%
“…For many patients with ESRD, kidney transplantation (KT) improves both survival and quality of life [1][2][3][4] ; however, the organ supply is limited, and careful patient selection is required to ensure equitable access to transplantation (ATT) for patients who stand to derive a survival benefit from transplantation (SBT). Studies of factors influencing ATT have identified a number of subgroup disparities that may not be explained by poor SBT, including patients of lower socioeconomic status, 5,6 black patients, 5,7-10 and obese patients.…”
mentioning
confidence: 99%